2021
DOI: 10.22320/07183607.2021.24.44.06
|View full text |Cite
|
Sign up to set email alerts
|

Clasificación espacial del suelo urbano por el valor especulativo del suelo e imágenes MSI satelitales usando K-MEANS, Huancayo, Perú

Abstract: The city of Huancayo, like other intermediate cities in Latin America, faces problems of poorly planned land-use changes and a rapid dynamic of the urban land market. The scarce and outdated information on the urban territory impedes the adequate classification of urban areas, limiting the form of its intervention. The purpose of this research was the adoption of unassisted and mixed methods for the spatial classification of urban areas, considering the speculative land value, the proportion of urbanized land,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Next, we applied the K-means algorithm, an unsupervised machine learning technique, to classify land use in the polder area using two years of data. Studies have shown that K-means is effective for image classification, urban spatial analysis, and land-use classification [28,29,34]. The land use categories considered in this study are shown in Figure 2.…”
Section: Datamentioning
confidence: 99%
“…Next, we applied the K-means algorithm, an unsupervised machine learning technique, to classify land use in the polder area using two years of data. Studies have shown that K-means is effective for image classification, urban spatial analysis, and land-use classification [28,29,34]. The land use categories considered in this study are shown in Figure 2.…”
Section: Datamentioning
confidence: 99%